Dynamics of peptide capsules in saline solutions - Whitaker, Susan Kathrine (Kansas State University, 2018)
Nanocapsules have become more popular as potential therapeutic agents in recent years. Though liposomes are the most popular and well-studied, nanocapsules made of peptides have their distinct advantages as the research behind them intensifies. Branched Amphiphilic Peptide Capsules (BAPCs) are a type of self-assembling nanocapsules that are made up of two similar branched, amphiphilic, chemically synthesized peptides. These peptides self-assemble into bilayer delimited capsules capable of encapsulating solutes and even small proteins in aqueous solution. Previous studies have shown that these nanocapsules are taken up by cells in culture without negative effects and can be given to an organism, distributed throughout the organism without cytotoxic effects, suggesting a possible future as a therapeutic nanoparticle. For use as a therapeutic system, the understanding of how these BAPCs behave in the presence of sodium and chloride, two very common biological ions, must be understood and characterized. Previously published work showed that the BAPC bilayer is semipermeable and excludes sodium and chloride ions. Current research has expanded on this. Besides being semipermeable, this bilayer is also a dynamic membrane that has the ability to expand and contract due to osmotic pressure from ions in solution. Eosin Y, an autoquenching dye, has been used for many of the studies to monitor the behavior and the amount of water within the BAPCs. Having insight into how the BAPCs change under physiological conditions is necessary if these nanoparticles are to be used in a clinical setting and may open doors to new uses.
Keywords: BAPC peptide capsule